2022
DOI: 10.15406/mojph.2022.11.00390
|View full text |Cite
|
Sign up to set email alerts
|

Assessing pesticides residue in water and fish and its health implications in the Ivo river basin of South-eastern Nigeria

Abstract: This study assessed the concentration of pesticides residue in an agriculturally endemic basin in southeastern Nigeria, where pesticide is freely used without any form of regulations. Analysis of water and fish from the streams and tributaries in the basin reveal a very high level of pollution from organochloride pesticides and atrazine which occur above international drinking water standards and at health hazard levels where ecosystem and human health can be compromised. Some of these chemicals have been outr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Other papers have listed records of Margaritifera auricularia (endemic to Southern Europe and currently named Pseudunio auricularius ), Gonidea sp. (endemic to western North America) and Margaritifera cardiidae from Nigeria (Akindele & Olutona, 2015; Gabriel et al, 2017; Victoria et al, 2022). The taxonomic placement of these records cannot be identified with certainty owing to the lack of specimen images and descriptions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other papers have listed records of Margaritifera auricularia (endemic to Southern Europe and currently named Pseudunio auricularius ), Gonidea sp. (endemic to western North America) and Margaritifera cardiidae from Nigeria (Akindele & Olutona, 2015; Gabriel et al, 2017; Victoria et al, 2022). The taxonomic placement of these records cannot be identified with certainty owing to the lack of specimen images and descriptions.…”
Section: Resultsmentioning
confidence: 99%
“…In most cases, the molluscs that were used in these studies were reidentified to the species or genus level, so the published data could be reused with the correct taxonomic names given in Appendix . In contrast, four publications that were based on unspecified Iridinidae from Nigeria (Abwage et al, 2022; Akindele & Olutona, 2015; Gabriel et al, 2017; Victoria et al, 2022) should be ignored by researchers, because freshwater mussel taxa in these articles could not be reidentified correctly owing to the lack of shell images and descriptions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the current results align with some but not all findings reported in previous studies assessing human health risks of trace elements in groundwater in the Niger Delta Region of Nigeria [91][92][93][94] . Specifically, several studies reported associations between the assessment of groundwater quality for drinking and irrigation purposes [4][5][6][7][8][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111] . The current study observed an association between some physicochemical indices and heavy metals.…”
Section: Bones and Jointsmentioning
confidence: 99%
“…It is a good carbohydrate source, which is commonly denoted to as the main body tissues fuel (Robert et al, 2000;Olalekan et al, 2018b) since it produces energy that the body requires to function effectively in its everyday activities. Human activities (human induced) may promote the occurrence of harmful pollutants such as cyanide as well as trace metals in cassava flour, rendering it unsafe for human utilization, particularly when they remain present in large concentrations (Raimi and Sabinus, 2017a;Suleiman et al, 2019;Raimi et al, 2019cRaimi et al, , 2020aRaimi et al, , 2022aIsah et al, 2020a,b;Morufu Olalekan et al, 2020a;Olalekan et al, 2021Olalekan et al, , 2022bHussain et al, 2021a,b;Morufu et al, 2021a;Asiegbu et al, 2022;Oshatunberu et al, 2023). In urban centers, the predominant cyanide sources as well as metal pollution remain anthropogenic (human actions), whereas contamination resulting from nature sources that predominates in remote areas (Raimi and Sabinus, 2017b;Olalekan et al, 2018b;Ogidi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%